Species composition of amphibians and reptiles in the Yen Tu mountain area, Bac Giang province - Tung, Tran Thanh; Ngat, Le Nguyen; Sang, Nguyen Van (Academia Journal of Biology, 2014)
The reptile and amphibian fauna of the Yentu mountain area, Bacgiang province is very rich in species composition, with 101 herptile species belonging to 5 orders, 25 families. Among them, 41 amphibian species (about 25.3% of total species of Vietnam) belonging to 8 families, 3 orders and 58 reptilian species (about 20.27% of total species of Vietnam) belonging to 17 families, 2 orders, were recorded in this area. 4 species of them were endemic of Vietnam; 20 species were listed in Red Data Book of Vietnam (2000); 11 species listed in the IUCN Red List (2004) and 11species listed in the Governmental Decree 32/2006 ND-CP. According to the list of Amphibians and Reptiles of Vietnam 2005 [14], 25 species were supplemented to the herpeto fauna of this area: Ichthyophis bannanicus, Leptobrachium chapaense, Bufo galeatus, Brachytarsophrys feae, Rana bacboensis, R. nigrovittata, Theloderma corticale, Kalophrynus interlineatus, Goniurosaurus lichtenfelderi, Draco maculatus, Eumeces elegans, Takydromus wolteri, Boiga multomaculata, Calamaria septentrionalis, Elaphe porphyracea, Rhynchophis boulengeri, Platysternon megacephalum, Cyclemys tcheponensis, Pyxidea mouhoti, Sacalia quadriocellata, Manouria impressa, Leptblalax pelodytoides, Polypedates maximus, Shinisaurus crocodilurus and Opisthotropis lateralis.